2020
DOI: 10.1109/access.2020.2972922
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Predict Essential Proteins Based on Diffusion Distance Networks

Abstract: Essential proteins are important for the survival and reproduction of organisms. Many computational methods have been proposed to identify essential proteins, due to the production of vast amounts of protein-protein interaction (PPI) data. It has been demonstrated that PPI networks have graphtheoretic characteristics as so-called small-world and scale-free. The traditional metrics cannot really reflect the relationship between proteins when identifying essential proteins from PPI networks. In this paper, we co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 39 publications
(61 reference statements)
0
12
0
Order By: Relevance
“…On the contrary, it is convenient and fast to predict their associations by computation methods. Recently, the application of computation methods in bioinformatics has attracted wide attention, such as identifying lncRNA and mRNA Co-expression Modules [14], calculating miRNA functional similarity [15], the discovery of miRNA-mRNA regulatory modules [16] [17], Predict Essential Proteins [18] [19], and the prediction of miRNAtarget interactions [20]. Before 2013, there was no computation methods to predict lncRNA-disease associations.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, it is convenient and fast to predict their associations by computation methods. Recently, the application of computation methods in bioinformatics has attracted wide attention, such as identifying lncRNA and mRNA Co-expression Modules [14], calculating miRNA functional similarity [15], the discovery of miRNA-mRNA regulatory modules [16] [17], Predict Essential Proteins [18] [19], and the prediction of miRNAtarget interactions [20]. Before 2013, there was no computation methods to predict lncRNA-disease associations.…”
Section: Introductionmentioning
confidence: 99%
“…There are various guises of network propagation, such as random walks on graphs [20], the Google PageRank search algorithm [21], heat diffusion processes [22], graph kernels [23], etc. In biological network, plenty of methods based on network propagation have been widely applied to essential proteins identification [24,25], drug synergy prediction [26], tumors classification [27], disease associated genes identification [28,29], microbedisease associations inference [30] and protein functions prediction [31], which demonstrated that network propagation is a powerful data transformation method of broad utility in genetic research [18]. Additionally, the rationality of combining the protein domain, complex information and PINs for functions prediction is substantiated by the DCS and DSCP methods.…”
Section: Introductionmentioning
confidence: 99%
“…There are various guises of network propagation, such as random walks on graphs [20], the Google PageRank search algorithm [21], heat diffusion processes [22], graph kernels [23], etc. In biological network, plenty of methods based on network propagation have been widely applied to essential proteins identification [24,25], drug synergy prediction [26], tumors classification [27], disease associated genes identification [28,29], microbe-disease associations inference [30] and protein functions prediction [31], which demonstrated that network propagation is a powerful data transformation method of broad utility in genetic research [18]. Additionally, the rationality of combining the protein domain, complex information and PINs for functions prediction is substantiated by the DCS and DSCP methods.…”
Section: Introductionmentioning
confidence: 99%